Factors That Influence Sustainable Regional Development - Yusri, Mohammad (Indonesian Journal Education, 2025)
This study aims to explore the key factors influencing sustainable regional development, particularly the expansion of urban spaces toward suburban areas. Using a qualitative descriptive method, data were collected through literature review and document analysis related to spatial planning, sustainability, and regional policies. The findings reveal six main factors that drive urban expansion: accessibility, public services, land characteristics, landowner behavior, regulatory frameworks, and developer initiatives. Areas with high accessibility and quality public services tend to attract population shifts from city centers to suburbs. Additionally, fertile land, proactive landowner behavior, supportive regulations, and strategic developer actions further contribute to suburban growth. Each of these factors interacts within the broader context of sustainable development, emphasizing the importance of balancing environmental preservation with socio-economic progress. The study provides a comprehensive understanding that can inform future spatial planning and policymaking for sustainable regional development.